Pattern of presentation of gliomas and clinical outcome - An institutional descriptive study - Arbaz Gul Abro,; Aleena Azam,; Pardeep Kumar,; Tazeen Fatima,; Shaheer Ali Mughal,; Fayaz Mangi, (LIAQUAT MEDICAL RESEARCH JOURNAL, 2024)
Gliomas are common brain tumours presenting with aggressive clinical behavior. There is limited literature available to evaluate clinical pattern and survival outcome in Pakistani population. The patients were retrieved from Cancer Research Database, (a complete set of clinical data of cancer patients from 2008 till 2023, prospectively established and regularly updated). There were 139 patients of primary brain tumors. Most common histological type of glioma was GBM (36%) and there was male preponderance. Majority of patients presented with high grade IV and stage 4 tumors. Surgery was frequently used primary therapy while radiotherapy was most frequently give second line therapy. Out of 79 patients 63 died because of disease, median survival time was 6 months, age and grade did not appear to show any significant influence on survival. Our study showed that glioma has male predominant tumour with aggressive clinical pattern and poor overall survival. Further studies to understand biology and genetic pattern of glioma and development of targeted therapy is recommended so that clinical outcome of these patients can be improved.